Synergistic Effect of Mitochondrial and Lysosomal Dysfunction in Parkinson’s Disease - Flora Guerra; Giulia Girolimetti; Raffaella Beli; Marco Mitruccio; Consiglia Pacelli; Anna Ferretta; Giuseppe Gasparre; Tiziana Cocco; Cecilia Bucci (Cells, 2019)
Crosstalk between lysosomes and mitochondria plays a central role in Parkinson’s Disease (PD). Lysosomal function may be influenced by mitochondrial quality control, dynamics and/or respiration, but whether dysfunction of endocytic or autophagic pathway is associated with mitochondrial impairment determining accumulation of defective mitochondria, is not yet understood. Here, we performed live imaging, western blotting analysis, sequencing of mitochondrial DNA (mtDNA) and senescence-associated beta-galactosidase activity assay on primary fibroblasts from a young patient affected by PD, her mother and a healthy control to analyze the occurrence of mtDNA mutations, lysosomal abundance, acidification and function, mitochondrial biogenesis activation and senescence. We showed synergistic alterations in lysosomal functions and mitochondrial biogenesis, likely associated with a mitochondrial genetic defect, with a consequent block of mitochondrial turnover and occurrence of premature cellular senescence in PARK2-PD fibroblasts, suggesting that these alterations represent potential mechanisms contributing to the loss of dopaminergic neurons.